Sistem Pendukung Keputusan Pemilihan Kepala Sekolah Berprestasi Menggunakan Metode SAW (Simple Additive Weighting) - Rajagukguk, Denni M; Ritonga, Indra Swanto (LPPM UNIKA Santo Thomas, 2020)
Selection of School Principals with Achievement in the Ministry of Education and Culture is a form of appreciation from the government for principals who have high achievement in the form of exemplary ways to improve the quality of education in schools and in their regions. Through this award, it is hoped that it can further motivate and improve the professionalism of school principals which in turn will improve the quality of national education. The problem in selecting outstanding principals is that the process of selecting outstanding principals is confusing and less optimal in making the selection and there is much interest in assessing school principals, so that the assessment is not carried out in a transparent manner. The design of decision support involves a method that has been widely used by researchers, namely the SAW (Simple Additive Weighting) Method, where the process is to find the weighted sum of the performance ratings for each alternative on all attributes. Decision support system testing will be carried out at the Education Office and all data relating to this decision support system will be coordinated with the Education Office.